DIRECT COSTING–THE CASE AGAINST. - Hepworth, Samuel R. (The Accounting Review, 1954)
Abstract The use of direct costing means its full fledged incorporation into the accounting process in terms of its effect on the determination of periodic net income and financial position. One of the most appealing results of the use of direct costing, particularly to the harassed and overworked cost accountants, is the elimination of all necessity of making any attempt to allocate fixed overhead costs, both initially to service and production departments and ultimately to units of product or jobs. Admittedly, simplicity in cost accounting methods with the attendant reduction in the cost of cost accounting represents a desirable objective, but only if the information produced by the simplified methods is not substantially less useful for internal managerial use as well as for use in reporting the operating results and financial position. An advantage often claimed for direct costing is that it focuses attention on the variable cost factors which are by their nature more subject to managerial control than those costs typically described as fixed. While it is perfectly true that management control is most important in connection with variable costs, it is difficult to see that direct costing offers more in this connection than a well organized system of standards for direct material, direct labor and variable overhead.